Efficient iterative solution of electromagnetic scattering using adaptive cross approximation enhanced characteristic basis function method. Issue 3 (1st February 2015) - Chen, Xinlei; Gu, Changqing; Li, Zhuo; Niu, Zhenyi
Abstract : A new hybrid adaptive cross approximation‐characteristic basis function method (ACA‐CBFM) is proposed to efficiently solve the electromagnetic scattering problems. In the conventional ACA‐CBFM, the ACA is only applied to speed up the construction of the reduced matrix that is directly solved and stored. However, with the increase of the size of the targets under analysis, the reduced matrix will become so large that it is difficult to directly solve and store. In this study, the reduced matrix is further compressed by the adaptive cross approximation‐singular value decomposition (ACA‐SVD) and solved by an iterative method, which leads to reduced storage and accelerated matrix vector product. Furthermore, the ACA‐SVD is adapted to efficiently generate the characteristic basis functions (CBFs), which reduces both the time of generating initial CBFs and the SVD time of initial CBFs. Numerical results about the electromagnetic scattering from perfect electric conducting targets are given to demonstrate the merits of the proposed methods.